Sensory outcome of exotropia surgery in Thailand: a retrospective multicenter study - Narisa Rattanalert; Supaporn Tengtrisorn; Supawan Surukrattanaskul; Phanthipha Wongwai; Nutsuchar Wangtiraumnuay; Wadakarn Wuthisiri; Suntaree Thitiwichienlert; Warassabhorn Ployprasith; Rattiya Pornchaisuree; Piangporn Saksiriwutto; Penny Singha; Warakorn Thiamthat; et al. (International Journal of Ophthalmology)
AIM: To evaluate the characteristics of exotropia (XT) and motor-sensory outcomes after surgical correction and to determine the factors associated with sensory outcomes of XT surgery. METHODS: The medical records of all patients that were diagnosed with XT and underwent strabismus surgery in 13 major government hospitals in Thailand; from January 2012 to December 2019, were retrospectively reviewed. Univariable and multivariable logistic regression were performed to identify factors related to binocular vision. RESULTS: Data of five hundred and thirty-seven patients were analyzed. Two hundred and twenty-six patients were men (42.1%). The median age of onset was 3 years old [Interquartile range (IQR): 1, 8]. The median age at diagnosis was 9.21 years old (IQR; 4.64, 21.06). intermittent exotropia [X(T)] was the most common type (52.1%); 19.5% of the patients had amblyopia. For refractive error, spherical equivalent refraction on right eye (RE) and left eye (LE) were -0.53±2.45 diopters (D) (range -14.88 to +10 D) and -0.48±2.37 D (range -19.50 to +7.75 D), respectively. The mean angle of deviation at distance and near before surgery were 42.06±14.91 prism diopters (PD) and 40.81±16.09 PD, respectively. Follow-up time after first operation was 2.48±2.27y. Four hundred sixty-two patients (86%) needed only one operation and 299 (55.6%) patients had bilateral lateral rectus recession. At final visit, the mean angles of deviation at distance and near decreased to 5.76±8.96 PD and 5.01±8.73 PD, respectively. After surgery, two hundred seventy-three patients (50.8%) were evaluated for binocular function, but the others did not have result. From multivariable logistic regression in 273 patients, the factors related to better binocular function were type of XT which was X(T) [adjusted odds ratio (aOR) 10.35; 95%CI: 4.73, 22.66] compared to constant XT, without amblyopia (aOR 3.97; 95%CI: 1.84, 8.53), underwent only single operation compared with more than 1 operation (aOR 3.80, 95%CI: 1.58, 9.16), the angle of deviation at near in last visit less than 10 PD better than 10–30 PD with aOR 0.42 (95%CI: 0.18, 0.96) and type of refraction revealed isometropia better than anisometropia with aOR 4.13 (95%CI: 1.19, 14.32). CONCLUSION: The surgical outcomes of XT within one operation in Thailand is 86%. The factors related to achieve binocular function includes type of XT as X(T), without amblyopia, angle of deviation at final visit less than 10 PD, isometropia type of refraction and underwent only one surgical correction.